Meningitis caused by Streptococcus pyogenes triggered by malignant otitis externa: A case report - Ayako Shirai; Daisuke Ono; Kazuyuki Mimura; Kei Yamamoto; Takayuki Kawamura; Yujin Nozaki; Sunao Tanaka; Masaomi Yamamoto; Hideaki Ohno; Kunihisa Tsukada; Hideaki Oka (IDCases)
A previously healthy 58-year-old male initially presented to a healthcare facility with otorrhea in his left ear, accompanied by a scab in both the auricle and ear canal, with a lesion protruding from the left cavity and oozing discharge (day 0). The following day, the patient was transferred to our facility with fever and altered consciousness. Imaging studies, including computed tomography and magnetic resonance imaging, revealed a soft tissue mass in the left maxillary, ethmoid and sphenoid sinuses, and diffuse pus within the subdural space over the bilateral frontoparietal regions. Cerebrospinal fluid (CSF) analysis showed elevated opening pressure, increased white blood cell count, predominance of polymorphonuclear leukocytes, elevated protein levels, and reduced glucose levels compared to the serum. Streptococcus pyogenes was identified in ear discharge, CSF, and blood cultures using matrix-assisted laser desorption ionization time-of-flight mass spectrometry. The presence of a papilloma in the left nasal cavity suggested that malignant otitis externa (MOE) served as the entry point for infection, leading to meningitis. The patient was treated with a combination of ceftriaxone and vancomycin, followed by ceftriaxone and cefotaxime, surgical resection of the tumor, and local debridement for infection control. To date, this is the first reported case of S. pyogenes-induced meningitis secondary to MOE. Although rare, the detection of S. pyogenes in otitis externa emphasizes the necessity of comprehensive evaluation of ear pathology to enable effectively source control as well as manage related infections and complications.